Application of soluble bio-organic substances (SBO) as photocatalysts for wastewater treatment: Sensitizing effect and photo-Fenton-like process - Gomis, J. (2013)
Soluble bio-organic substances (SBO) isolated from urban biorefuses have been investigated in photocatalytic processes for wastewater treatment using a cationic dye, namely crystal violet (CV) as target compound. The SBO have been found to enhance the photobleaching of CV solutions with an optimal SBO concentration of ca. 20 mg L⁻¹. Mechanistic investigation based on chemical probes and changes in the absorption spectrum of CV in the presence of SBO seems to indicate that a complex formed between sensitizer and substrate plays a major role in the process. SBO have also been tested for the implementation of photo-Fenton processes at circumneutral media: the observed pseudo first order rate constants for CV decoloration was higher for UV/SBO/Fe(II)/H₂O₂ (5.5 × 10⁻³ min⁻¹) than for UV/Fe(II)/H₂O₂ (1.5 × 10⁻³ min⁻¹). A modified mechanism, in which HO· are less relevant that at the acidic medium, is in agreement with results of experiments carried out with chemical probes.